2012
DOI: 10.1002/cphc.201100790
|View full text |Cite
|
Sign up to set email alerts
|

Intercage Electron Transfer Driven by Electric Field in Robin–Day‐Type Molecules

Abstract: A new class of isomers, namely, intercage electron-transfer isomers, is reported for fluorinated double-cage molecular anion e(-)@C(20)F(18)(NH)(2)C(20)F(18) with C(20)F(18) cages: 1 with the excess electron inside the left cage, 2 with the excess electron inside both cages, and 3 with the excess electron inside the right cage. Interestingly, the C(20)F(18) cages may be considered as two redox sites existing in a rare nonmetal mixed-valent (0 and -1) molecular anion. The three isomers with two redox sites may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 42 publications
3
12
0
1
Order By: Relevance
“…The delocalization error has been implicated in difficulties calculating alkylcobalamins [GNPM13], where HF-DFT might be very helpful. It has also been useful in analyzing intercage electron transfer in Robin-Day type molecules [WLZL12], and a large density-driven error has been found in the Kevan model of a solvated electron [JOD13]. IR spectra of small anionic water clusters have been shown to be problematic with fixed basis DFT calculations, and fixed by MP2 [GDTJ15].…”
Section: E Applications Of Energy-error Analysis and Other Approachesmentioning
confidence: 99%
“…The delocalization error has been implicated in difficulties calculating alkylcobalamins [GNPM13], where HF-DFT might be very helpful. It has also been useful in analyzing intercage electron transfer in Robin-Day type molecules [WLZL12], and a large density-driven error has been found in the Kevan model of a solvated electron [JOD13]. IR spectra of small anionic water clusters have been shown to be problematic with fixed basis DFT calculations, and fixed by MP2 [GDTJ15].…”
Section: E Applications Of Energy-error Analysis and Other Approachesmentioning
confidence: 99%
“…As a result, local electric fields from molecular dipoles and ions affect ET [94][95][96][97][98][99], providing a promising means for increasing the efficiency of the desired CT processes while suppressing the undesired ones. Small dipolar moieties modify the electron affinity and the ionization energy of materials [100][101][102][103][104].…”
Section: Dipole Effects On Charge Transfermentioning
confidence: 99%
“…To improve stabilities of general solvated electrons, in our recent series of papers, [24][25][26][27][28][29] basing on the synthesized C 20 F 20 and potential C 24 F 24 and C 60 F 60 cage, 30,31 we have constructed a series of interesting cage-like single molecular solvated (di)electron systems with large stabilities due to the using covalent cages: e@C 60 F 60 , e 2 @C n F n (n=20, 28, 36, 50, 60, and 80), e@C 20 F 18 (NH) 2 C 20 F 18 , and e@C 24 F 22 (NH) 2 C 20 F 18 , which shows these perfluorinated cages are efficient containers of excess electrons. For these cages, the dipole moments of all the exo polarized C δ+ -F δ-bonds of each cage are directed toward the center of the cage to form an interior electronic attractive potential (IEAP) which can help to trap excess electron(s) inside these cages.…”
Section: Introductionmentioning
confidence: 99%
“…Also, basing on triple-cage-like electride salt K + [e@3C 8 (O)] -, Li et al, also suggested 33 that multicage strategy is effective to enhance nonlinear optical (NLO) response. For the double-cage-like single molecular solvated single electron systems e -@C 20 F 18 (NH) 2 C 20 F 18 , [26][27][28] the excess electron can be trapped inside different cages to form interesting inter-cage electron transfer isomers. 26 In this case, besides the double-cage-like single molecular solvated electron systems, 20,21,[26][27][28] We are interesting in the influence of the number of cage units on the localizations and spin states of two excess electrons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation